An exploration of Echinoderes (Kinorhyncha: Cyclorhagida) in Korean and neighboring waters, with the description of four new species and a redescription of E. tchefouensis Lou, 1934 - Sørensen, Martin V.; Rho, Hyun Soo; Min, Won-Gi; Kim, Dongsung; Chang, Cheon Young (Zootaxa, 2012)
A large collection of kinorhynch specimens from coastal and subtidal localities around the Korean Peninsula and in the East China Sea was examined, and the material included several species of undescribed or poorly known species of Echinoderes Claparède, 1863. The present paper is part of a series dealing with echinoderid species from this material, and inludes descriptions of four new species of Echinoderes, E. aspinosus sp. nov., E. cernunnos sp. nov., E. microaperturus sp. nov. and E. obtuspinosus sp. nov., and redescriprion of the poorly known Echinoderes tchefouensis Lou, 1934.